DESIGN AND DEVELOPMENT OF MONTELUKAST SODIUM FAST DISSOLVING FILMS FOR BETTER THERAPEUTIC EFFICACY - Vishvakarma, Prabhakar (Journal of the Chilean Chemical Society, 2018)
The oral route is most popular route for the administration of therapeutic agents because of the low cost of therapy and ease of administration lead to high levels of patient compliance. The most popular oral solid dosage forms are tablets and capsules. Many patients find it difficult to swallow tablets and hard gelatin capsules particularly pediatric and geriatric patients and do not take their medicines as prescribed. The objective of this research was to prepare fast dissolving oral thin film (FDOTF) containing Montelukast sodium is indicated for the prophylaxis and chronic treatment of asthma to enhance convenience and compliance to the elderly and pediatric patients for better therapeutic efficacy. The present investigation was undertaken with the objective of formulating of the montelukast sodium fast dissolving oral thin films allowing fast reproducible drug dissolution in oral cavity thus bypassing first pass metabolism. The film were prepared by using polymers such as hydroxypropyl methyl cellulose (HPMC) and Maltodextrin, plasticizer such as PEG 400, by a solvent casting method. They were evaluated for physical characteristics such as thickness, uniformity of weight, folding endurance, drug content, surface ph, percentage elongation and tensile strength, drug polymers compatibility by FTIR study, scanning electron microscopy and in vitro drug release. The formulations were subjected to disintegration, in-vitro drug release test. The in vitro disintegration time of the optimized batch F4 was found to be 20 sec. The optimized batch was found to be stable for 1 month under specified stability conditions.